(untitled) (REVISTA POIÉSIS, 2019)
This text concentrates on creative dialogues shaped by fine art students together with elderly residents from Strovolos III, displaced housing estate in Nicosia. Such neighbourhood became the classroom for the module Public Art and Socially Engaged Practices of the Fine Art program of the Uni-versity of Nicosia in the academic year 2017-2018 in collaboration with Artos Foundation. Students collaborated with the residents of Strovolos III to shape a series of creative mappings and actions.